A Socio-Economic Overview of Majeng Ikan Partnership: A Profit-Sharing Analysis within the Framework of Sharia Economic Law - Seniati; Nilfatri; Wandi; Pitri, Alisyah; Okva Marwendi, Reza (Journal of Economics and Social Sciences (JESS), 2025)
The study purpose was to examine the implementation of profit-sharing systems in the traditional majeng ikan practice in Lambur Luar Village, Tanjung Jabung Timur, from the perspective of Islamic economic law. The research aimed to analyze how local profit-sharing mechanisms align with Sharia principles such as mudharabah, musyarakah, and ijarah, despite the absence of formal contracts. It also sought to identify challenges faced in contract clarity, transparency, and fairness within community-based economic cooperation. Ultimately, the study intends to propose Sharia-compliant solutions that strengthen the sustainability of traditional fishing economies through improved legal awareness and ethical practice. Results. The research found that majeng ikan profit-sharing reflects the core values of Islamic economics—justice, trust, and mutual consent—even though it relies on unwritten agreements. Profit-sharing typically follows a 50:50 ratio between net owners and fishermen, aligning with the mudharabah contract model. However, issues such as verbal-only agreements and limited understanding of Sharia contracts create vulnerabilities to disputes and exploitation. The study also observed adaptive features such as non-cash distribution and spontaneous mutual aid, which strengthen household resilience but require clearer ethical and legal safeguards.